2007
DOI: 10.1093/rheumatology/kem372
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in proteins of the cryopyrin inflammasome influences susceptibility and severity of rheumatoid arthritis (The Swedish TIRA project)

Abstract: Compound polymorphisms in CIAS1 and TUCAN associate with RA susceptibility and severity. The cryopyrin inflammasome needs further attention regarding a possible aetiopathogenetic connection with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
108
4
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 22 publications
9
108
4
1
Order By: Relevance
“…119 Moreover, in a Swedish cohort, RA susceptibility and severity are significantly influenced by the combination of the Q705K variant of NLRP3, already known for its low-penetrance in FCAS, and the C10X variant of caspase recruitment domain family, member 8. 120 Notably, these two polymorphisms are highly recurrent: Q705K polymorphism in NLRP3 was found in 6.5% of the Caucasian population and CARD-8 gene polymorphism C10X is present in 40%. 121,122 However, their penetrance in the pathogenesis of immune-immune mediated disorders is very low, and leads to susceptibility to autoimmunity only when in combination.…”
Section: Adaptive Immunity-mediated Diseasesmentioning
confidence: 99%
“…119 Moreover, in a Swedish cohort, RA susceptibility and severity are significantly influenced by the combination of the Q705K variant of NLRP3, already known for its low-penetrance in FCAS, and the C10X variant of caspase recruitment domain family, member 8. 120 Notably, these two polymorphisms are highly recurrent: Q705K polymorphism in NLRP3 was found in 6.5% of the Caucasian population and CARD-8 gene polymorphism C10X is present in 40%. 121,122 However, their penetrance in the pathogenesis of immune-immune mediated disorders is very low, and leads to susceptibility to autoimmunity only when in combination.…”
Section: Adaptive Immunity-mediated Diseasesmentioning
confidence: 99%
“…Genetic variants in the genes encoding for proteins of the NLRP3 inflammasome have been studied in association with various inflammatory diseases (6)(7)(8)(9)(10)(11). Germline alterations in the NLRP3 gene encoding the NLRP3 protein have been associated with susceptibility to different inflammatory disorders such as hereditary periodic fever syndromes including familial cold urticaria, Muckle-Wells syndrome and neonatal-onset multisystem inflammatory disease (also known as chronic infantile neurologic cutaneous and arthropathy syndrome) (4,(11)(12)(13) leading to the constitutive activation of NLRP3 and subsequent overproduction of IL-1β (3).…”
Section: Introductionmentioning
confidence: 99%
“…Germline alterations in the NLRP3 gene encoding the NLRP3 protein have been associated with susceptibility to different inflammatory disorders such as hereditary periodic fever syndromes including familial cold urticaria, Muckle-Wells syndrome and neonatal-onset multisystem inflammatory disease (also known as chronic infantile neurologic cutaneous and arthropathy syndrome) (4,(11)(12)(13) leading to the constitutive activation of NLRP3 and subsequent overproduction of IL-1β (3). Several recent studies have also revealed the association of the Q705K polymorphism in the NLRP3 gene (rs35829419) with various inflammatory diseases including celiac disease (9), diabetes type-1 (8), abdominal aortic aneurysms (14), Crohn's disease (15) and rheumatoid arthritis (10 CARD8 (C10X) genes was found to be associated with rheumatoid arthritis (10) and Crohn's disease (15,16). Considering a possible key role of the NLRP3 inflammasome in promoting myocardial inflammation (17) and athero sclerosis through the production of pro-inflammatory cytokine IL-1β (18), the aim of the present study was to investigate the effect of Q705K polymorphism in NLRP3 gene and the risk of developing MI in a northern Swedish population.…”
Section: Introductionmentioning
confidence: 99%
“…5,27,28 Subsequent reports found that patients homozygous for the C10X polymorphism still expressed an immunoreactive isoform of CARD8, although at a reduced level. 29 Recently, variants in another component of the NALP3 inflammasome, NALP3 and/or NOD2, and a combination of NALP3 (Q705K) and CARD8 (C10X) genotypes, were found to be associated with disease severity of rheumatoid arthritis 30,31 and CD in the absence of NOD2 mutations. 32,33 Analysis of CARD8, NALP3 and NOD2 in the Korean UC and CD patients of this study found no evidence of NALP3 or NOD2 association with either disease.…”
Section: Introductionmentioning
confidence: 99%